The Railways Act, 1921, (11 and 12 Geo. V. Ch. 55). Notes and observations. Mainly for the information of the staff employed in the Railway Service of Great Britain. [With forew. by A.G. Walkden] (The Gray's Inn Press, 1922)
With index and tabs.